Statistical control charts to assess the incidence of presumably infectious diarrhea reported between 2009 and 2019 in children under 4 years of age in the macro regions of Araçatuba, Marília and Presidente Prudente, São Paulo, Brazil. - Navas-Úbida, Suelen; Giuffrida, Rogério (Población y Salud en Mesoamérica, 2021)
Objective: To evaluate the monthly rates of hospitalizations for childhood diarrhea in macro-regions of Araçatuba, Marília and Presidente Prudente, SP, between 2019 -June Between June 2009. Methods: The average rates and their standard deviations for admission of diarrhea in the target population were obtained from DATASUS and standardized for cases x 100,000 inhabitants. Confidence limits were established, occurrences above confidence limits were considered epidemic events. The normality of the data and serial autocorrelation were tested using the Shapiro-Wilk and Durbin-Watson method. Results: All methods detected epidemic occurrences in the three regions. Araçatuba and Marília, the peaks were concentrated in the first half of the decade and Presidente Prudente, close to the middle. The CUSUM method was more sensitive to detect epidemic periods, however the normality data and assumptions have been violated by serial autocorrelation in a few months. The EWMA method was considered the most appropriate. Conclusions: Statistical process control charts can be used to monitor and compare disease incidence between different regions.